Factor the Expression: Finding Common Terms in 9a+8a

Question

We factored the expression 9a+8a 9a+8a into its basic terms:

9a+8a 9\cdot a+8\cdot a

Take out the common factor from the factored expression.

Step-by-Step Solution

We start with the expression 9a+8a 9a+8a .

First, we notice that both terms share a common factor of a a .

So, we factor outa a from each term:

9a=a9 9a=a\cdot9 and 8a=a8 8a = a\cdot 8 .

This allows us to rewrite the expression as a(9+8) a(9+8) .

Thus, the factored form is a(9+8) a\left(9+8\right) .

Answer

a(9+8) a\left(9+8\right)